2018
DOI: 10.3126/jkahs.v1i2.24128
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of HPV DNA Test versus Pap Smear in the Screening of Cervical Cancer

Abstract: Introduction: Cancer cervix is a common genital cancer. Human papillomavirus is the main cause of cervical cancer because of the strong association of certain HPV genotypes and the development of cervical cancer and its precursor lesions, cervical intraepithelial neoplasia CIN 2 or CIN3. Methods: The study was conducted on 180 gynecological patients seen at the outpatient department of Manipal Hospital, Bangalore. A comparative study of HPV DNA test with Pap smear in the screening of cervical neoplasia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In the present study sensitivity, specificity, PPV, NPV and accuracy of MI score for predicting malignancy in ovarian tumors was 1.00, 0.818, 0.529, 1.00 and 0.849 respectively. Similar results were observed by Sassoneet al 13,14…”
Section: Discussionsupporting
confidence: 91%
“…In the present study sensitivity, specificity, PPV, NPV and accuracy of MI score for predicting malignancy in ovarian tumors was 1.00, 0.818, 0.529, 1.00 and 0.849 respectively. Similar results were observed by Sassoneet al 13,14…”
Section: Discussionsupporting
confidence: 91%
“…HPV testing and Pap smear did not differ significantly for detecting LSIL in their study. Though HPV testing alone proved to be promising for primary cervical screening in the study conducted in India by Pradhan et al, the study was conducted in a small sample size [25]. The cost effectiveness is the limitation for implementation of HPV testing in cervical cancer screening in the countries like India and Nepal with low resource setting.…”
Section: Discussionmentioning
confidence: 99%
“…[4,23] Many included multiple technologies in their studies (such as ThinPrep Pap test, SurePath Pap test, and/or other technologies not approved by the FDA) [5,17]. [25]. In contrary, an 11-year retrospective study conducted in Korea by Kang et al demonstrated that Pap smear had greater sensitivity and specificity for detecting HSIL and SCC when compared to HPV testing [26].…”
Section: Discussionmentioning
confidence: 99%
“…If a cell abnormality is detected, the technician can test the remaining specimens for HPV using HPV DNA testing without collecting new epithelial cells. After that, treatment planning can be continuously carried out (Pradhan et al, 2018).…”
Section: Research Articlementioning
confidence: 99%